Is Investment in Preprimary Education Too Low? Lessons from (Quasi) Experimental Evidence across Countries - Holla, Alaka (World Bank, Washington, DC, 2021)
A large body of evidence suggests sizeable improvements in cognitive and social-emotional skills and subsequent educational attainment following preprimary education interventions as well as increases in earnings later in life. Yet, while the world has nearly reached universal primary education, coverage of early childhood education is still low in many countries. This study uses a novel global dataset of effect sizes from more than 50 studies conducted in 19 countries to examine measures of school participation, cognitive skills, social-emotional skills, and behavior, both during and after preprimary ages. Estimates from meta-regression analysis suggest both strong demand for preprimary services when offered and significant improvements in children’s cognitive skills (0.15 sd) and their executive functioning, social-emotional learning, and behavior (0.12 sd) during the pre-primary period. Moreover, our meta-analytic results indicate statistically significant persistent advantages (0.07 sd) in each type of skill beyond the preprimary period. Pooled heterogeneous treatment effects also suggest higher gains for disadvantaged children. Lastly, cost-benefit analysis using studies from low- and middle-income countries implies benefit-to-cost ratios ranging between 1.7 and 14.2, suggesting high returns to preprimary investments even in contexts with limited state capacity.